دور وأهمية الإعلان في بناء العلامة التجارية دراسة ميدانية على مستهلكي المنظفات في الساحل السوري - ديوب محمد عباس; الجاسم محمد; سليمان نبيله محمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول البحث مفهوم العلامة التجارية وأهميتها بالنسبة إلى المنظمات والمستهلكين. و يتناول أيضاً الإعلان كعنصر ترويجي مهمّ جداً في بناء العلامة التجارية والتعريف بدلالاتها ومعانيها الرمزية, وإقناع المستهلكين بها, وذلك باستخدام وسائل الإعلام المناسبة, والتصميمات الإعلانية المبدعة والخلاقة, فالإعلان الذي ينال إعجاب المستهلكين يحقق نتائج باهرة. يعرض هذا البحث الأساس النظري والعلمي للعلامة التجارية, ودور الإعلان في بنائها, واختبار الفرضيات التي تدور حول أثر كل من العلامة التجارية والإعلان للعلامة التجارية على مستهلكي المنظفات في الساحل السوري. وتم التوصل إلى مجموعة من النتائج وأهمها: أ‌- تفضل المنظفات التي تحمل علامة تجارية مميزة على المنظفات التي لا تحمل علامة تجارية. ب‌- يخلق الإعلان الثقة بالعلامة التجارية, مما يجعل عملية التغيير عنها صعبة, ويصبح هناك نوع من التبني لهذه العلامة من قبل المستهلكين. The research is about the concept of the brand and its importance to the organizations and consumers. It also shows the advertisement as an important popularity element in constructing the brand and making its symbolic concepts and meanings clear, and persuading the consumers with it, by using the suitable media, and the creative adverts designs, since the advertisements that the consumers admire give great results. The research shows the scientific and theoretical basis of the brand, and the role of the advertisements in creating it, and tests the hypothesis about the effect of the brand and its advertising on the consumers in the Syrian Coast. Some of the important results are: a- The cleaners with a brand are preferred to those without, b- The advertisement creates confidence in the brand, so the consumers adopt it and never changes their opinion about it easily.